2021
DOI: 10.29130/dubited.1013082
|View full text |Cite
|
Sign up to set email alerts
|

Berezin Number Inequality for Increasing Operator Convex Function

Abstract: olan üretici çekirdekli ℋ(𝛺) Hilbert uzayı üzerinde 𝐴 sınırlı lineer operatör için Berezin sembolü ve Berezin sayısı sırasıyla 𝐴 ̃(𝜆) ≔ 〈𝐴𝐾 𝜆 , 𝐾 𝜆 〉 ℋ ve 𝑏𝑒𝑟(𝐴) ≔ 𝑠𝑢𝑝 𝜆∈𝛺 |𝐴 ̃(𝜆)| biçiminde tanımlanır. Bu karakteristik ifadeler kullanılarak 𝑏𝑒𝑟(𝐴) ≤ 1 √2 𝑏𝑒𝑟(|𝐴| + 𝑖|𝐴 * |) eşitsizliği elde edilmiştir. Bu çalışmamızda ise onlar arasındaki diğer eşitsizlikler ispatlanmış ve Berezin sayı eşitsizlikleri için operatör konveks fonksiyonlarının bazı uygulamaları verilmiştir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…for 𝑟 ≥ 1 and for any 𝑇, 𝑅 ∈ ℒ(ℋ). One year later, the same authors (Huban et al, 2021b;Huban et al, 2022a) found the inequalities…”
Section: 𝑏𝑒𝑟(𝑇) ≤ 𝑤(𝑇)mentioning
confidence: 94%
See 2 more Smart Citations
“…for 𝑟 ≥ 1 and for any 𝑇, 𝑅 ∈ ℒ(ℋ). One year later, the same authors (Huban et al, 2021b;Huban et al, 2022a) found the inequalities…”
Section: 𝑏𝑒𝑟(𝑇) ≤ 𝑤(𝑇)mentioning
confidence: 94%
“…Some inequalities have been demonstrated using the Hermite-Hadamard inequality. These inequalities are a revised version of Huban et al (Huban et al, 2021b;Huban et al, 2022a) and Başaran et al (Başaran et al, 2022).…”
Section: 𝑏𝑒𝑟(𝑇) ≤ 𝑤(𝑇)mentioning
confidence: 99%
See 1 more Smart Citation